The effects of poverty on environmental sustainability: the case study of the Kassena-Nankana West District, Upper East Region - Abuchow, Justice (2016)
A thesis submitted to the Department Of Geography and Rural Development, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the degree of Master of Philosophy.